An Analysis of the State’s Role in Regulating and Supervising E-Money Providers as a Form of Digital Consumer Protection - Wibowo, Andi Wisnu; Hariansah, Syafri (Universitas Islam Sultan Agung, 2025)
This research analyzes the state's role in regulating and supervising e-money providers in Indonesia as a form of digital consumer protection. The rapid development of financial technology has introduced various digital payment innovations, but also creates regulatory challenges and risks for consumers. This study evaluates the effectiveness of the regulatory framework implemented by Indonesian financial authorities in supervising e-money providers and identifies gaps in digital consumer protection mechanisms. The research employs a normative juridical approach with a comparative analysis of e-money regulations in other countries. The findings indicate that despite various regulations governing e-money, weaknesses remain in transactional supervision, consumer education, and digital dispute resolution. The research recommends strengthening the supervisory capacity of financial authorities, establishing integrated complaint handling mechanisms, and enhancing consumer digital literacy. These findings contribute to the development of a more adaptive regulatory framework centered on consumer protection within the evolving digital financial ecosystem.